Saint Odd [large type] : an Odd Thomas novel - Koontz, Dean R. (Dean Ray), 1945- (Koontz, Dean R. (Dean Ray), 1945- Odd Thomas novel., 2015)
Odd Thomas is back where it all started . . . because the time has come to finish it. Since he left his simple life in the small town of Pico Mundo, California, his journey has taken him to places strange and wonderful, mysterious and terrifying. Again and again, he's gone where he must and done what he had to do. Every triumph has been hard won. Each sacrifice has taken its toll. But for Odd Thomas, the wandering is done. Only the reckoning remains.